Testing loan loss provisioning hypotheses for banks in China from 2011 to 2016 - Bingqing, Pu (2017)
Loan Loss Provision (LLP) is recognized as a layer of buffer that cover the potential loss from non-performing loans. There are substantial incentives in practical for managers to manipulate LLP. In China, the LLP is gradually becoming complete in China since it was established and the regulatory has put more attention on the supervision of the LLP in banking sector. Previous study has studied Chinese banks’ incentives to use LLP as a tool for different purpose, but most of them just focus on one or two theories and lack of a comprehensive investigation. This paper tests Loan Loss Provisioning behavior of Chinese banks over the period from 2011 to 2016. We firstly employed Stochastic frontier analysis to estimate the cost efficiency scores. Then, Generalised Method of Moments (GMM) Model is used to test the four hypotheses, namely, Income Smoothing, Capital Management, Business cycle and Banks Efficiency. In the results, Chinese banks do not show a pro or counter cyclical income smoothing. However, the study accepts the capital management and the business cycle hypotheses test, which suggests that LLP is used as a tool for capital management and a pro-cyclical provisioning behavior. In addition, banks exhibit a counter cyclical bank efficiency provisioning behavior.